Radiographic assessment of distribution of mandibular third molar impaction: A retrospective study - Tejavathi Nagaraj; Lakshmi Balraj; Keerthi Irugu; Shruthi Rajashekarmurthy; Sreelakshmi (Wolters Kluwer Medknow Publications, 2016)
Introduction: Third molars are the most common teeth that may follow an abortive eruption path and become impacted as a result of pathology, anatomical structures or insufficient osseous space posterior to the second molars. Aims and Objectives: The present study evaluated (1) the distribution of the impaction of mandibular third molar; (2) the distribution of the patterns of impaction radiographically; and (3) the gender distribution for pattern of impaction. Materials and Methods: This hospital-based retrospective study was conducted over a course of 6 months in the Department of Oral Medicine and Radiology and presents the analysis of 122 panoramic radiographs of patients between the age group of 18-30 years. They were interpreted and assessed for the impaction of mandibular third molars. Statistical analysis was done by Chi-square test. Results: Bilateral impaction of mandibular third molar is more common than unilateral in both the sexes, with mesioangular being the most common pattern. In males, mesioangular pattern was followed by horizontal, whereas in females it was followed by vertical. Conclusion: The present study provides useful data regarding the radiographic status of impacted mandibular third molars in patients.